Environmental Literacy, Green Culture, Environmental Awareness and Pro-Environmental Awareness: Evidence from Higher Education Industries - Rizal, Ach. Syaiful; Utami Ady, Sri (Akuntansi dan Teknologi Informasi, 2026)
Abstract Aim: This study aims to examine how environmental literacy, green culture, and environmental awareness relate to pro-environmental awareness among university students in Indonesia. Method: A quantitative approach was applied using a structured questionnaire distributed randomly to 124 accounting students at a university in East Java. The questionnaire covered environmental literacy, green culture, environmental awareness, and pro-environmental awareness indicators. The data were analysed using Partial Least Squares (PLS) to test both measurement and structural models. Findings: The results show that green culture is the only variable that significantly influences pro-environmental behaviour, while environmental literacy and awareness do not show direct effects. Implications: The findings imply that strengthening campus culture is more effective than relying solely on environmental knowledge or awareness campaigns. Universities should focus on creating an institutional atmosphere that models sustainable values through visible practices, leadership commitment, and collective participation. Environmental literacy and awareness remain important, yet they must be integrated into daily routines and social norms to drive real behavioural change. In short, sustainability education should move beyond theory and be embedded into the culture of the institution to encourage lasting pro-environmental behaviour among students. Novelty: The novelty of this study lies in its clear evidence that pro-environmental behaviour among university students depends more on the shared cultural environment than on individual knowledge or awareness. While many earlier studies highlighted literacy and awareness as key drivers, this study shows that cultural influence through norms, values, and institutional engagement plays a stronger role in shaping actual behaviour. So, the study adds a fresh perspective to sustainability research and challenges the assumption that knowledge alone can lead to behavioural change.